Open-Market Operations in a Model of Regulated, Insured Intermediaries - Bryant, John; Wallace, Neil (Journal of Political Economy, 1980)
In "The Inefficiency of Interest-bearing National Debt" (J.P.E. [April 1979]), we argued that private sector transaction costs are needed in order to explain interest on government debt. It follows that if the government's transaction costs do not depend on its portfolio, then, barring special circumstances, an open-market purchase is deflationary and welfare improving. In this paper we show that this result can survive a potentially relevant special circumstances: reserve requirements which limit the size of insured intermediaries.